Developmental validation of a fully integrated sample-to-profile rapid human identification system for processing single-source reference buccal samples. (May 2015) - Jovanovich, Stevan; Bogdan, Greg; Belcinski, Richard; Buscaino, Jacklyn; Burgi, Dean; Butts, Erica L.R.; Chear, Kaiwan; Ciopyk, Brian; Eberhart, David; El-Sissi, Omar; Franklin, Helen; Gangano, Stefanie; et al.
Graphical abstract: Highlights: Development of an easy to use, sample-to-profile DNA identification system, the RapidHIT ® System. Developmental validation of PowerPlex 16 HS RapidHIT chemistry for reference samples on the RapidHIT System. 88% first-pass, concordant full CODIS profiles for buccal swabs with 89% median peak height ratios. Full profiles obtained from 176 ng of saliva DNA applied to swabs. Abstract: Short tandem repeat (STR) DNA typing is a global standard for human identification. Current practice involves highly trained forensic analysts, operating in a laboratory setting, using multiple instruments to process samples and analyze the data. Here, we report the developmental validation of a fully integrated and automated DNA profiling system, the RapidHIT ® System, capable of producing up to five high quality STR profiles with full controls in approximately 90 min using PowerPlex ® 16 HS RapidHIT chemistry. The system integrates all sample handling steps: starting from lysis of cells on buccal swabs or other buccal sample types through DNA extraction, normalization, amplification, capillary array electrophoresis, detection, and integrated software analysis. The results describe the developmental validation of the RapidHIT™ System for buccal samples processed with the DNA IQ™ extraction chemistry using a guandinium chaotropic agent and paramagnetic beads followed by amplification using a modified version of PowerPlex 16 HS chemistry (PowerPlex 16 HS RapidHIT chemistry), and capillary electrophoresis with manual review of genotyping data following interpretation guidelines. All processing from the buccal swab to generation and processing of the profile occurs on the RapidHIT platform. Result: are concordant with traditional methods, with 88% first pass success rates for both the CODIS and PowerPlex 16 loci. Average peak height ratios were 0.89 for buccal swabs. The system produces full profiles from swabs with at least 176 ng of saliva DNA. Rapid DNA identification systems will significantly enhance capabilities for forensic labs, intelligence, defense, law enforcement, refugee and immigration applications, and kinship analysis.